Structural insight into hybrid peptide ε-helices. Issue 14 (23rd January 2020) - Misra, Rajkumar; George, Gijo; Reja, Rahi M.; Dey, Sanjit; Raghothama, Srinivasarao; Gopi, Hosahudya N.
Abstract : Unique ε-helical organizations (11-helices) from β, γ-hybrid peptides composed of chiral β 3 -amino acids along with achiral 3, 3- or 4, 4-dimethyl substituted γ-amino acids are disclosed. Abstract : Unique ε-helical organizations (11-helices) from β, γ-hybrid peptides composed of chiral β 3 -amino acids along with achiral 3, 3- or 4, 4-dimethyl substituted γ-amino acids are disclosed.